A birefringent polarization modulator: Application to phase measurement in conoscopic interference patterns - Veiras, Francisco Ezequiel (2016)
Conoscopic interferometry for crystal characterization is a very well known technique with increasing applications in different fields of technology. The advantage of the scheme proposed here is the introduction of a polarization modulator that allows the recovery of the phase information contained in conoscopic interferograms. This represents a real advantage since the most relevant physical information of the sample under study is usually contained in the phase of the fringe pattern. Moreover, this technique works successfully even when there are no visible fringes. The setup employed is a simple conoscopic interferometer where the elements under study correspond to two birefringent crystal slabs and a commercial mica wave plate. It allows the crystals to be characterized and the wave plate retardance to be measured as a function of the angle of incidence. The modulator itself consists of a single tiltable crystal plate which, by means of phase shifting techniques, permits the recovery of a phase map for each sample.  It is inexpensive and it can be easily calibrated, so it works with a wide range of phase shifting interferometry algorithms. We show that our scheme is easily adaptable to algorithms that require either a low or high amount of interferograms.